Polyion liquid binder and synthetic method and application thereof

Through polyion liquid binders based on halogenated styrene derivatives and imidazole derivatives, the shortcomings of the conductive binders in existing lithium-ion batteries in terms of ionic conductivity and cyclic performance are solved, and higher mechanical strength and ionic conductivity are achieved, which extends the cycle life of the electrode and improves the overall performance of lithium-ion batteries.

CN119751724APending Publication Date: 2025-04-04ZHEJIANG UNIV OF TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411851623.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing lithium-ion battery conductive adhesives have shortcomings in improving the ionic conductivity and cycling properties of the electrodes, and the polymer chain rigidity and low conductivity of conventional polymer binders limit the further development of lithium-ion batteries.

Method used

Polyionic liquid binders based on halogenated styrene derivatives and imidazole derivatives are prepared by quaternization and polymerization reactions, with excellent mechanical strength and ionic conductivity.

Benefits of technology

This polyion liquid binder significantly improves the structural integrity and ionic conductivity of the electrode in lithium-ion batteries, extends the cycle life of the electrode, and reduces the glass transition temperature and polymer ions binding, enhancing the charge and discharge rate and overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751724A_ABST
    Figure CN119751724A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion battery binders, and relates to a polyion liquid binder as well as a synthesis method and application thereof. The polyion liquid binder is prepared by the following steps: carrying out quaternization reaction on a halogenated styrene derivative and an imidazole derivative to generate quaternary ammonium salt, and carrying out polymerization reaction in the presence of an initiator to obtain the polyion liquid binder. The polyion liquid prepared by the preparation method disclosed by the invention, as a conductive adhesive, not only has excellent adhesive property and mechanical strength, can effectively improve the structural integrity and electronic connection of an electrode in a cycle process and prolong the cycle life of the electrode, but also has lower glass transition temperature and high ionization degree than a conventional polymer, and is suitable for being used in the field of electrochemical devices. The constraint of the polymer on ions is greatly reduced, so that the conductivity of the ions is enhanced. And meanwhile, the preparation method and process are simple, are suitable for industrial large-scale preparation, and have wide market application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium battery binders, and specifically relates to a polyionic liquid binder based on halogenated styrene derivatives and imidazole derivatives, a synthesis method thereof, and an application thereof as a conductive binder for lithium ion batteries. Background Art

[0002] Lithium-ion batteries are new green high-energy secondary batteries that appeared in the early 1990s and have become the focus of research and development in countries around the world. Binders are an important component of lithium-ion batteries. Their biggest role is to tightly connect the electrode material with the collector liquid, reduce the loss of active materials, and maintain the stability of the entire electrode. With the increasing demand in the battery market, the development of lithium-ion battery binders has also been very rapid. In the past few decades, from traditional polyvinylidene fluoride (PVDF) binders, carboxymethyl cellulose (CMC) binders, styrene-butadiene rubber (SBR) binders and polyacrylic acid (PAA) binders, natural polysaccharide polymer binders, synthetic polymer binders, to composite polymers and functional special polymer binders, the sources of binders have become more and more abundant, and their varieties have become more and more abundant.

[0003] However, these conventional polymer binders generally have the properties of high molecular chain rigidity and low electrical conductivity, which seriously restricts the further development of lithium-ion batteries. Therefore, functional binders have attracted more and more attention from researchers.

[0004] For example, CN115966653A discloses a composite conductive adhesive of polyacrylic acid and carbon nanotubes, and CN115895547A discloses a composite conductive adhesive of epoxy resin and modified graphene. The addition of carbon nanotubes and modified graphene gives the adhesive a certain conductivity, which improves the electronic conductivity of the electrode. CN115028813A discloses a conductive polymer adhesive based on a polyfluorene structure. A large number of fluorene structures on the polymer main chain form a conjugated effect by π-π stacking, which has a smaller impedance, better conductivity and smaller voltage polarization compared with PVDF. However, whether lithium ions can be quickly embedded and extracted between the positive and negative electrodes is the essence of whether lithium ion batteries can charge and discharge quickly and improve cycle and rate performance. Therefore, having higher ionic conductivity on the surface and inside of the electrode is the key to improving the performance of lithium ion batteries.

[0005] As a new type of functional polymer material, polyionic liquids have significant advantages such as non-flammability, non-volatility, wide electrochemical window, high thermal stability and easy processing. They also have a lower glass transition temperature and a softer molecular chain structure than conventional polymer binders, which facilitates the rapid migration of ions in electrode materials. In addition, the high ionization degree of polyionic liquids significantly reduces the binding effect of polymers on ions, further enhancing their ionic conductivity. These advantages enable polyionic liquids to effectively improve the ionic conductivity of electrode materials and promote the rapid intercalation and deintercalation of lithium ions during the charge and discharge process, thereby improving the charge and discharge rate and overall performance of lithium-ion batteries. Therefore, the development of polyionic liquids with higher ionization degrees and adjustable properties, and further expanding their applications in energy storage and conversion devices, has important research significance and practical value. Summary of the invention

[0006] The present invention aims at the deficiencies of many problems in the current conductive adhesives for lithium ion batteries, and provides a polyionic liquid adhesive and a preparation method thereof and its application in lithium ion batteries. The polyionic liquid adhesive provided by the present invention has sufficient bonding performance and mechanical strength, can ensure the structural integrity of the electrode during the cycle, and has a lower glass transition temperature than conventional polymer adhesives, and the molecular chain is softer, which is conducive to the rapid migration of ions. In addition, with high ionization degree, the polyionic liquid greatly reduces the binding of polymers to ions and enhances the conductive performance of ions. In addition, the preparation method of the adhesive of the present invention is simple and environmentally friendly, more suitable for industrial large-scale production, and has broad prospects for industrial application.

[0007] The technical solution of the present invention is described in detail below.

[0008] The present invention provides a method for synthesizing a polyionic liquid binder, wherein the method is to synthesize and polymerize an imidazole derivative and a halogenated styrene derivative to obtain the polyionic liquid binder. The innovation of the present invention is that the conductive polymer binder has excellent mechanical strength and ionic conductivity. The synthesis method comprises the following steps:

[0009] (1) heating a halogenated styrene derivative and an imidazole derivative to carry out a quaternization reaction to generate a quaternary ammonium salt;

[0010] (2) The product obtained in step (1) is dissolved in a solvent as a polymerization monomer, an appropriate amount of initiator is added, and a polymerization reaction is carried out under the protection of an inert gas to obtain a polyionic liquid binder.

[0011] Preferably, in step (1), the halogenated styrene derivative is selected from at least one of 4-chloromethylstyrene, 4-bromomethylstyrene, 4-chloroethylstyrene, 4-bromoethylstyrene, 4-chlorostyrene, and 4-bromostyrene; and the imidazole derivative is selected from at least one of 1-propylimidazole, 2-(1-imidazolyl)methyl acetate, 2-(1-imidazolyl)ethyl acetate, and 2-(1-imidazolyl)butyl acetate.

[0012] Preferably, in step (1), the imidazole derivative is slightly excessive, and the mass ratio of the halogenated styrene derivative to the imidazole derivative is 1:1-1.5.

[0013] Preferably, in step (1), the reaction solvent is a polar organic solvent. More preferably, the reaction solvent is anhydrous methanol.

[0014] Preferably, in step (1), the reaction temperature is 55-75°C and the reaction time is 5-20 hours; more preferably, a spherical condenser is used for reflux and the reaction is heated at 55-75°C for 5-20 hours. A more preferred temperature is 75°C for 20 hours. An oil bath is more preferred for heating.

[0015] Preferably, in step (1), the reaction process is monitored by thin layer chromatography (TLC) analysis. After the reaction is completed, the product is separated and purified, washed, and dried to finally obtain a yellow oily substance, which is stored at low temperature.

[0016] More preferably, in step (1), after the reaction is completed, the solvent is distilled off by vacuum distillation, and the water bath temperature is 20-40° C. More preferably, the water bath temperature is 35° C.

[0017] More preferably, in step (1), if impurities appear in the reaction or the reaction is incomplete, it is necessary to purify the product by column chromatography. It is more preferred to use dry loading. It is more preferred to use silica gel to mix the sample and then perform dry loading. It is necessary to first evaporate most of the solvent with a circulating water pump, and then evaporate the solvent completely with a mechanical oil pump (manifested by the silica gel powder no longer bubbling). More preferably, the elution solvent combination is a dichloromethane / methanol system or an ethyl acetate / methanol system. A more preferred combination is a dichloromethane and ethanol system. It is more preferred that the temperature of the rotary evaporator water bath cannot exceed 40°C.

[0018] Preferably, in step (2), the solvent required for the polymerization reaction is at least one of nitrogen-nitrogen dimethylformamide, dimethyl sulfoxide, nitrogen methyl pyrrolidone, methanol, and acetonitrile; more preferably, it is ultra-dry molecular sieve DMF or redistilled DMF. More preferably, it is redistilled DMF.

[0019] Preferably, in step (2), the initiator is one of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, azoisobutylcyanoformamide, ammonium persulfate, potassium persulfate, and sodium persulfate. More preferably, the initiator is azobisisobutyronitrile.

[0020] Preferably, in step (2), the amount of initiator used accounts for 1%-5% of the weight of the monomer, and the greater the amount of initiator used, the smaller the molecular weight of the obtained product. The more preferred amount of initiator used is 2%-3%.

[0021] Preferably, in step (2), the reaction temperature should be 35-75°C, the reaction time should be 5-20 hours, and more preferably, heating is performed by oil bath or water bath. More preferably, heating is performed by 70-75°C oil bath for 20 hours.

[0022] Preferably, in step (2), the inert gas is at least one of nitrogen, helium and argon.

[0023] In step (2) of the present invention, the long-chain polymer obtained has a positively charged quaternary ammonium group (-NR4 + ), a large number of ions can shuttle freely between polymer chains, promoting the movement of ions, thereby improving ionic conductivity. In addition, polyionic liquids have a lower glass transition temperature and more flexible molecular chains, which further promotes the movement of ions.

[0024] Preferably, in the step (2), after the reaction is completed, the reaction mixture is slowly poured into a small polar organic solvent to precipitate, the solid is separated by centrifugation, washed with a small polar organic solvent for multiple times, and then vacuum dried. More preferably, the small polar organic solvent is at least one of ethyl acetate, ether, petroleum ether, and n-hexane. More preferably, the small polar organic solvent is ethyl acetate or n-hexane. More preferably, the vacuum oven temperature for vacuum drying is 40-60° C., and the drying time is 20-40 hours.

[0025] The present invention also provides a polyionic liquid binder synthesized by any of the above-mentioned synthesis methods. More preferably, when the polyionic liquid binder is prepared as a binder solution with a mass fraction of 10%, the viscosity is 500-1200 mPa·s.

[0026] The present invention also provides the application of the polyionic liquid binder in the field of lithium ion battery binders. Preferably, the lithium ion battery is prepared by conventional methods.

[0027] Preferably, the polyionic liquid binder is used as a conductive binder in the preparation of lithium battery electrodes and / or lithium batteries. More preferably, the electrode is a positive electrode or a negative electrode, and the active material includes but is not limited to LFP, NCM532, NMC811, Si, and C.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] (1) The polyionic liquid binder synthesized in the present invention has excellent bonding properties and mechanical strength as a lithium-ion battery binder, can effectively improve the structural integrity and electronic connection of the electrode during the cycle process, and prolong the cycle life of the electrode. In addition, it has a lower glass transition temperature and a higher degree of ionization than conventional polymers, which greatly reduces the binding of the polymer to ions, thereby enhancing the conductivity of the ions.

[0030] (2) The raw materials used in the synthesis method of the present invention are widely available and easy to obtain, and are easy to implement industrially; the preparation process is simple and low in cost, and is suitable for industrial large-scale preparation.

[0031] (3) The polyionic liquid binder synthesized in the present invention has a lower glass transition temperature and higher ionization degree than conventional polymers. A large number of ions can freely shuttle between polymer chains, and the molecular chains are more flexible, which greatly reduces the binding of polymers to ions, thereby enhancing the conductivity of ions and having broad market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Attached Figure 1 This is a process flow chart of the present invention for synthesizing a polyionic liquid binder using halogenated styrene derivatives and imidazole derivatives;

[0033] Attached Figure 2 It is the synthetic route diagram of Example 1;

[0034] Attached Figure 3 is the H NMR spectrum of the monomer of Example 1;

[0035] Attached Figure 4 is the first charge and discharge curve diagram of Example 1;

[0036] Attached Figure 5 1 is a cycle performance diagram of Example 1 and Comparative Example 1;

[0037] Attached Figure 6 is a cycle performance diagram of Example 2;

[0038] Attached Figure 7 It is the scanning electron microscope image of Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0039] In order to better clarify and understand the purpose, process scheme and advantages of the present invention, the technical scheme and implementation method of the present invention are further described clearly, completely and in detail through specific examples and in combination with the accompanying drawings. It should be noted that the embodiments described in the present invention are implemented on the premise of the technical scheme of the present invention, and detailed implementation methods and specific operating processes are given, but they are only part of the embodiments of the present invention, not all of the embodiments. The specific implementation methods described are limited to explaining and interpreting the present invention, and do not limit the present invention. Based on the embodiments in the present invention, all other implementation methods obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0040] The experimental methods and conditions used in the embodiments of the present invention are conventional methods and conventional conditions unless otherwise specified. The materials, reagents or instruments used in the embodiments, unless otherwise specified, can be obtained from commercial sources or prepared by conventional methods. The reaction conditions embodied in the content of the invention of the present invention can achieve the reaction and obtain the product of the expected effect. Due to space limitations, some embodiments are listed below to further illustrate the advantages of the technical solution of the present invention.

[0041] Example 1

[0042] Take 1g 4-chloromethylstyrene and 1.2g 1-propylimidazole and add them to a round-bottom flask, then add 3ml anhydrous methanol to the flask, condense and reflux, and react at 60°C for 15 hours. After the reaction is completed, the methanol is evaporated, the product is washed with anhydrous ether 3 times and then spin-dried to obtain a yellow oily substance cmsIm2g. 2gcmsIm is used as a monomer, dissolved in 4ml ultra-dry DMF, and 40mg of AIBN is added, poured into a three-necked flask, sealed, nitrogen replaced three times, and reacted in an oil bath at 65°C for 20 hours. After the reaction is completed, the reaction mixture is slowly poured into 100ml ethyl acetate, and a white or light yellow solid PcmsIm will immediately precipitate. The solid is separated by centrifugation, washed with ethyl acetate several times, and vacuum dried at 40°C for 20 hours.

[0043] An electrode was made using the polyionic liquid binder PcmsIm prepared in Example 1 according to the following method.

[0044] The PcmsIm solid was dissolved in water to prepare a binder solution with a mass fraction of 10%, and the viscosity was measured to be 1000mPa·s. LFP, the aforementioned binder solution and the conductive agent (acetylene black or SuperP) were weighed and mixed into a slurry in a mass ratio of 8:1:1, coated on aluminum foil, dried in an oven at 80°C for 6 hours, and cut into pole pieces, with the metal lithium sheet as the negative electrode, the electrolyte being 1mol / L LiPF6 / EC–DMC (1:1), and the polypropylene microporous film as the diaphragm, and assembled into a simulated lithium-ion battery. Figure 4 It is the first charge and discharge curve of the corresponding battery in the voltage range of 2.5–4.0V at a rate of 0.2C. Figure 5 The long cycle performance of the corresponding battery is shown in the voltage range of 2.5–4.0 V at a rate of 1C, indicating that the polyionic liquid binder PcmsIm has excellent cycle performance when applied in LFP material.

[0045] On the basis of Example 1, the reaction conditions were changed to obtain the viscosity of the polymer solution as shown in the following table:

[0046]

[0047] Example 10

[0048] Take 1g 4-chloromethylstyrene and 1.2g 2-(1-imidazolyl) methyl acetate and add them to a round-bottom flask, then add 3ml anhydrous methanol to the flask, condense and reflux, and react at 60°C for 15 hours. After the reaction is completed, the methanol is evaporated, the product is washed with anhydrous ether 3 times and then spin-dried to obtain a yellow oily substance cmsIm-OR2g. 2gcmsIm is used as a monomer, dissolved in 4ml ultra-dry DMF, and 40mg of ABVN is added, poured into a three-necked flask, sealed, nitrogen replaced three times, and reacted in an oil bath at 65°C for 20 hours. After the reaction is completed, the reaction mixture is slowly poured into 100ml ethyl acetate, and a white or light yellow solid PcmsIm-OR will immediately precipitate. The solid is separated by centrifugation, washed with ethyl acetate several times, and vacuum dried at 40°C for 20 hours.

[0049] The PcmsIm-OR solid was dissolved in water to prepare a binder solution with a mass fraction of 10%. LFP, binder and conductive agent were weighed and mixed into a slurry in a mass ratio of 8:1:1. The slurry was coated on aluminum foil and dried in an oven at 80°C for 6 hours before being cut into pole pieces. The metal lithium sheet was used as the negative electrode, the electrolyte was 1 mol / L LiPF6 / EC–DMC (1:1), and the polypropylene microporous film was used as the separator to assemble a simulated lithium-ion battery. The measured battery has good cycle performance at a rate of 1C ( Figure 6 ), indicating that the polyionic liquid binder PcmsIm-OR can be used in LFP materials.

[0050] Comparative Example 1

[0051] Polyvinylidene fluoride (PVDF) was dissolved in NMP to prepare a binder solution with a mass fraction of 4% and a viscosity of 1000 mPa·s. LFP, binder and conductive agent were weighed and mixed into a slurry in a mass ratio of 8:1:1, coated on aluminum foil, and cut into pole pieces after vacuum drying in an oven at 80°C for 6 hours. The metal lithium sheet was used as the negative electrode, the electrolyte was 1 mol / L LiPF6 / EC–DMC (1:1), and the polypropylene microporous film was used as the diaphragm to assemble a simulated lithium-ion battery. Figure 5 The long cycle performance of the battery tested in the voltage range of 2.5-4.0V at a rate of 1C for the corresponding batteries of Example 1 and Comparative Example 1 is shown in the figure. As can be seen from the figure, the long cycle performance test of Example 1 and Comparative Example 1 shows that the electrode of Example 1 has better cycle stability. The capacity of Comparative Example 1 decays rapidly after less than 200 cycles, while Example 1 can stably cycle 300 cycles, and the electrode of Example 1 has a higher coulombic efficiency than the electrode of Comparative Example 1, indicating that lithium ions are fully embedded and extracted, which is due to the rapid ion transport characteristics of the polyionic liquid binder.

[0052] Figure 7 It is the scanning electron microscope image of Example 1 and Comparative Example 1. Through scanning electron microscope comparison, after 300 cycles, the electrode of Comparative Example 1 (i.e., PVDF binder) showed obvious wide and deep cracks, while Example 1 (polyionic liquid binder) only showed tiny and shallow cracks, indicating that the polyionic liquid has stronger bonding properties and mechanical strength.

[0053] The above-mentioned specific implementation modes are preferred examples of the present invention. Although they are relatively detailed, they cannot limit the claims of the present invention. Any changes, modifications, substitutions, combinations, and simplifications made using the technical contents disclosed by the present invention should be equivalent embodiments and do not deviate from the technical features of the present invention. They still belong to the scope of the technical features of the present invention and should be included in the protection scope of the present invention.

[0054] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for synthesizing a polyionic liquid binder, characterized in that: The following steps are involved: (1) heating a halogenated styrene derivative and an imidazole derivative to carry out a quaternization reaction; (2) The obtained product is dissolved in a solvent as a polymerization monomer, an appropriate amount of initiator is added, and a polymerization reaction is carried out under the protection of an inert gas to obtain a polyionic liquid binder.

2. The method for synthesizing a polyionic liquid binder according to claim 1, characterized in that: In the step (1), the halogenated styrene derivative is selected from at least one of 4-chloromethylstyrene, 4-bromomethylstyrene, 4-chloroethylstyrene, 4-bromoethylstyrene, 4-chlorostyrene, and 4-bromostyrene; the imidazole derivative is selected from at least one of 1-propylimidazole, 2-(1-imidazolyl)methyl acetate, 2-(1-imidazolyl)ethyl acetate, and 2-(1-imidazolyl)butyl acetate.

3. The method for synthesizing a polyionic liquid binder according to claim 1, characterized in that: The mass ratio of the halogenated styrene derivative to the imidazole derivative in the step (1) is 1:1-1.

5.

4. The method for synthesizing a polyionic liquid binder according to claim 1, characterized in that: The reaction solvent in step (1) is a polar organic solvent.

5. The method for synthesizing a polyionic liquid binder according to claim 1, characterized in that: The reaction temperature of step (1) is 55-75° C., and the reaction time is 5-20 hours.

6. The method for synthesizing a polyionic liquid binder according to claim 1, characterized in that: The initiator in step (2) is one of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, azoisobutylcyanamide, ammonium persulfate, potassium persulfate, and sodium persulfate, and the amount used is 1%-5% of the monomer mass.

7. The method for synthesizing a polyionic liquid binder according to claim 1, characterized in that: The reaction temperature of step (2) is 35-75° C., and the reaction time is 5-20 hours.

8. The method for synthesizing a polyionic liquid binder according to claim 1, characterized in that: The reaction solvent of step (2) is at least one of nitrogen-nitrogen dimethylformamide, dimethyl sulfoxide, nitrogen methyl pyrrolidone, methanol and acetonitrile.

9. A polyionic liquid binder prepared according to the synthesis method according to any one of claims 1 to 8.

10. Use of the polyionic liquid binder prepared by the synthesis method according to any one of claims 1 to 8 in the field of lithium batteries.

Citation Information

Patent Citations

  • Conductive binder as well as preparation method and application thereof

    CN115028813A

  • Polymer matrix composite with laser-induced metallization characteristic

    CN104672890A

  • Preparation method of quaternary ammonium salt ionic liquid polymer

    CN108070049A

  • Lithium battery, binder of lithium battery, electrode plate, battery cell and preparation method of binder

    CN116731228A

  • Solid polymer electrolyte, negative plate containing solid polymer electrolyte, and preparation method and application of solid polymer electrolyte

    CN118173877A